Pola Resistensi Bakteri Terhadap Antibiotik Pada Penderita Ulkus Diabetikum Di RSUP Dr. Soeradji Tirtonegoro Klaten Periode September 2014-Agustus 2015 - Farida, Hijri Ismi; , Prof.Dr. M. Kuswandi, SU., M.Phil., Apt (2016)
Diabetic foot ulcer is characterized by open foot wounds in diabetic patients. If the infection is not properly treated the severity of infection will increase. A potent antibiotic against microorganism is needed for treating the infection. Increasing the use of antibiotics will have an impact on the development of bacterial resistance to antibiotics. The aim of this study was to determine the antibiotic resistance pattern of bacteria in patients with diabetic foot ulcer at X Hospital during September 2014-August 2015. This study was non experimental study with descriptive analytic method. This study with a retrospective design involved data collection from patient medical records, bacteria culture results, and antibiotic susceptibility testing results. The data were analyzed to determine the most bacteria to cause infection, the antibiotic resistance pattern of bacteria, and the appropriate use of antibiotic based on bacteria culture results and antibiotic susceptibility testing results. A total of 25 pathogens from 45 patients with diabetic foot ulcer were identified. Enterococcus sp. was the most bacteria found on infected foot wounds in diabetic patients 11 (13,4%), followed by Klebsiella sp. 9 (11,0%), and Staphylococcus aureus 8 (9,8%). Enterococcus sp. was resistant to meropenem (64%), amikacin (91%), ceftriaxon (82%), and cefixime (91%), then Klebsiella sp. and Staphylococcus aureus was resistant to ampicillin (100% and 67%). A total of 31,3% definitive antibiotics given to diabetic foot ulcer patients were appropriate with culture results and antibiotic susceptibility testing result. Keywords: Resistance pattern, diabetic foot ulcer, antibiotic